Extracellular Vesicle-Encapsulated miR-29b-3p Released From Bone Marrow-Derived Mesenchymal Stem Cells Underpins Osteogenic Differentiation - Zhang, Xueliang; Wang, Wenji; Wang, Yongping; Zhao, Haiyan; Han, Xingwen; Zhao, Tong; Qu, Peng (Frontiers in Cell and Developmental Biology, 2021)
Objective: Mesenchymal stem cells (MSCs) confers therapeutical benefits in various pathologies and cancers by releasing extracellular vesicles (EVs) loaded with bioactive compounds. Herein, we identified bone marrow MSCs (BMSCs)-derived EVs harboring microRNA (miR)-29b-3p to regulate osteogenic differentiation through effects on the SOCS1/NF-κB pathway via targeting of KDM5A in osteoporosis. Methods: We quantified the miR-29b-3p in BMSCs-derived EVs from bone marrow specimens of osteoporotic patients and non-osteoporotic patients during total hip arthroplasty (THA). miR-29b-3p targeting KDM5A was confirmed by promoter luciferase assay and enrichment of KDM5A in the promoter region of SOCS1 was analyzed by ChIP. The expression and translocation of NF-κB to the nucleus was detected by Western blot analysis and immunofluorescence staining, respectively. An OVX osteoporosis mouse model was established to further confirm the in vitro findings. Results: BMSC-derived EVs of osteoporotic patients exhibited downregulated miR-29b-3p. EV-encapsulated miR-29b-3p from BMSCs potentiated osteogenic differentiation by specifically inhibiting KDM5A. KDM5A inhibited osteogenic differentiation by the regulation of H3K4me3 and H3K27ac of SOCS1. SOCS1 potentiated osteogenic differentiation by inhibiting NF-κB pathway. Conclusion: EV-encapsulated miR-29b-3p-derived from BMSCs potentiated osteogenic differentiation through blockade of the SOCS1/NF-κB pathway by inhibition of KDM5A.